STATUS KESUBURAN KIMIA TANAH DI KECAMATAN MAPANGET KOTA MANADO - Nining Soleman; Jenny J. Rondonuwu; Sandra Pakasi (COCOS, 2018)
ABSTRACT Â The study aimed to determine the soil chemical fertility status in Mapanget District, Manado City. This research was conducted from January to April 2018. The research method used is the survey method, where soil samples are taken at six points based on land use. Nutrients analyzed were Nitrogen (Kjedhal Method), Phosphorus (Bray I Method), Potassium (Bray I Method), Organic C (Walkley and Black Method) and pH (Kjedhal Method). The data obtained were analyzed descriptively. The results showed that soil pH in the study location was in the range of 6.49 to 6.80, the elemental content of nitrogen was in the range of 0.15% to 0.24%, the content of phosphorus was in the range of 11.56 ppm to 23.16 ppm, the content of Potassium is in the range of 14.58% to 33.65%, and the C-organic content is in the range of 1.87% to 2.22%. Â Keywords : Nitrogen, Phosphorus, Potassium, C-organic, pH